Flipbook Development As Learning Media For Bali Aga Spices Through 4D Model - Putri, Made Anggun Riani; Sukerti, Ni Wayan; Masdarini, Luh (Jurnal Pendidikan Tata Boga dan Teknologi, 2025)
This study aims to develop a learning media in the form of a flipbook on the topic of traditional Balinese spices (basa) from the Bali Aga community in the Culinary Bali course, using the 4D development model (Define, Design, Develop, Disseminate). The research employed a Research and Development (R&D) approach, with validation subjects consisting of material experts and media experts. Data were collected through validation questionnaires and analyzed descriptively, both qualitatively and quantitatively.The Define stage was carried out through needs analysis and identification of Bali Aga spices. The Design stage involved structuring the flipbook content, including classification, functions, and visualization of traditional spices. The Develop stage produced the flipbook prototype, which was validated by experts. The results showed that the flipbook obtained an average score of 97% from material experts and 95% from media experts, both categorized as “very valid.” The Disseminate stage was conducted by sharing the flipbook digitally through a YouTube link, enabling wider access for students and the public.The findings indicate that the developed flipbook is feasible and valid as a learning medium for the Culinary Bali course. This research was limited to expert validation and dissemination, without measuring student responses or learning effectiveness.